Salt-tolerant endophytic bacterium Enterobacter ludwigii B30 enhance bermudagrass growth under salt stress by modulating plant physiology and changing rhizosphere and root bacterial community - Wei, Hongjian; He, Wenyuan; Li, Ziji; Ge, Liangfa; Zhang, Juming; Liu, Tianzeng (Frontiers in Plant Science, 2022)
Osmotic and ionic induced salt stress suppresses plant growth. In a previous study, Enterobacter ludwigii B30, isolated from Paspalum vaginatum, improved seed germination, root length, and seedling length of bermudagrass (Cynodon dactylon) under salt stress. In this study, E. ludwigii B30 application improved fresh weight and dry weight, carotenoid and chlorophyll levels, catalase and superoxide dismutase activities, indole acetic acid content and K+ concentration. Without E. ludwigii B30 treatment, bermudagrass under salt stress decreased malondialdehyde and proline content, Y(NO) and Y(NPQ), Na+ concentration, 1-aminocyclopropane-1-carboxylate, and abscisic acid content. After E. ludwigii B30 inoculation, bacterial community richness and diversity in the rhizosphere increased compared with the rhizosphere adjacent to roots under salt stress. Turf quality and carotenoid content were positively correlated with the incidence of the phyla Chloroflexi and Fibrobacteres in rhizosphere soil, and IAA level was positively correlated with the phyla Actinobacteria and Chloroflexi in the roots. Our results suggest that E. ludwigii B30 can improve the ability of bermudagrass to accumulate biomass, adjust osmosis, improve photosynthetic efficiency and selectively absorb ions for reducing salt stress-induced injury, while changing the bacterial community structure of the rhizosphere and bermudagrass roots. They also provide a foundation for understanding how the bermudagrass rhizosphere and root microorganisms respond to endophyte inoculation.